Extraction of essential oil derivatives from pomegranate seeds using different solvents - Yap Phooi Fung (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
This project mainly focuses on the extraction efficiency of essential oil derivatives from pomegranate seeds via atmospheric pressure extraction and high pressure extraction methods. For atmospheric pressure extraction methods, experimental works involved water-bath extraction, soxhlet extraction and ultrasonic-assisted extraction were conducted. Different solvents (hexane, cyclohexane, diethyl ether) and extraction time (2 - 4 hours) were manipulated to investigate the effect of the extraction conditions on the extraction methods. The experimental result shows that the ultrasonic-assisted extraction was the most efficient extraction method, by using hexane, at four hours extraction time, to obtain the highest yield of essential oil derivatives, 23.775 %. In the case of high pressure extraction method, Polymath 6.1 Software was used to conduct the simulation works of supercritical CO2 extraction. Supercritical CO2 was used as the solvent. The yield of essential oil derivatives at different operating conditions was re-extracted from the published paper, to simulate the mole fraction of punicic acid dissolved in supercritical CO2. The results show that the highest mole fraction of punicic acid dissolved in supercritical CO2, 0.998863460, was obtained at 313.15 K, 40,000 kPa, at three hours extraction. The relationship between the experimental pressures (operating pressures) with the mole fraction of punicic acid dissolved in supercritical CO2 was proved, by comparing with the theoretical pressures calculated from Equation of State (Peng-Robinson Equation).